Monte-Carlo Serpent code validation based on the experimental data from research subcritical facility - O. P. Trofymenko; A. V. Nosovsky; V. I. Gulik (Ядерна фізика та енергетика)
Description of computation model for Kyoto University Critical Assembly (KUCA) developed with the help of Monte-Carlo Serpent code was presented in this paper. The simulation of criticality and subcriticality condi-tions for KUCA was carried out. The effective multiplication factors for different critical experiments were calcu-lated for KUCA. The presented obtained results were considered and compared with the experimental data and with computation results from other Monte Carlo codes.